2007
DOI: 10.1128/jvi.02422-06
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus-Induced Neuroinflammation: Glial Infection and Capsid Protein-Mediated Neurovirulence

Abstract: West Nile virus (WNV) infection causes neurological disease at all levels of the neural axis, accompanied by neuroinflammation and neuronal loss, although the underlying mechanisms remain uncertain. Given the substantial activation of neuroinflammatory pathways observed in WNV infection, we hypothesized that WNV-mediated neuroinflammation and cell death occurred through WNV infection of both glia and neurons, which was driven in part by WNV capsid protein expression. Analysis of autopsied neural tissues from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 69 publications
7
111
0
Order By: Relevance
“…Indeed, the WNV C protein is reportedly neurotoxic in vivo (Yang et al, 2002), a finding that we have confirmed in separate studies (G. van Marle et al, 2007). The mechanism of pathogenesis is not known, but it is interesting to note that the C protein binding region of I2…”
Section: Discussionsupporting
confidence: 59%
“…Indeed, the WNV C protein is reportedly neurotoxic in vivo (Yang et al, 2002), a finding that we have confirmed in separate studies (G. van Marle et al, 2007). The mechanism of pathogenesis is not known, but it is interesting to note that the C protein binding region of I2…”
Section: Discussionsupporting
confidence: 59%
“…Indeed, infected astrocytes have been detected in some fatal human cases of WNV encephalitis, suggesting that these cells are also targeted by WNV in vivo (41). We observed both a delay in the kinetics of WNV-MAD78 replication and a reduction in peak infectious particle production in astrocytes compared to WNV-NY.…”
Section: Discussionmentioning
confidence: 57%
“…First, the restricted replication of WNV-MAD78 in astrocytes may minimize the initial amplification of virus and reduce the rate of spread within the CNS, thus allowing more time for the host innate and adaptive immune responses to clear the virus prior to widespread infection of highly susceptible neurons. Second, as with other disease states, WNV infection induces astrocytes to release neurotoxic factors that exacerbate neuropathology (41). Therefore, suppression of viral replication within astrocytes may reduce the extent of bystander cell death of uninfected neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNS response to ischaemia, degenerative diseases and viral infection is largely manifested by neuronal loss and inflammatory responses (Gao et al, 2002;Liao et al, 2002;Chen et al, 2004;Raung et al, 2005;German et al, 2006;Ovanesov et al, 2006;Ghoshal et al, 2007;van Marle et al, 2007;Saxena et al, 2008;Swarup et al, 2008). Generally, the onset and/or interactive crosstalk of neuronal injury and neuroinflammation play a critical role in the pathogenesis of neurological disorders.…”
Section: Introductionmentioning
confidence: 99%